Diffusion MRI-based analysis of functional alterations of the glymphatic system in children with non-lesional epilepsy - Bixia Wu; Gengbiao Zhang; Yanting Wang; Hongyi Zheng; Hui Tan; Wenbin Zheng (Neuroimage: Reports)
Objective: Based on diffusion tensor imaging (DTI) data, we used DTI-analysis along the perivascular space (DTI-ALPS) and free-water mapping to investigate the function of the glymphatic system and its relationship with clinical features among pediatric patients with magnetic resonance imaging (MRI)-negative non-lesional epilepsy (NLE). Methods: A total of 83 NLE children (mean age 9.25 ± 4.07 years) and 45 matched healthy controls (mean age 9.36 ± 3.89 years) were recruited. All eligible patients were routinely scanned by 3.0T MRI to rule out organic lesions, and DTI data were collected at the same time. The ALPS index and fractional volume of free water in white matter (FW-WM) in the brain were calculated to analyze the differences between groups and the correlation between the corresponding parameters and clinical indicators such as age of onset, duration of the disease, seizure frequency, and seizure duration. Results: The NLE group had significantly lower ALPS indexes in the left (ALPS-L, F = 4.415, p = 0.038) and right (ALPS-R, F = 12.673, p = 0.001) cerebral hemispheres compared to the HC group. ALPS-L was positively correlated with age of onset (r = 0.322, p = 0.008) and negatively correlated with FW-WM (r = −0.337, p < 0.001). Free-water mapping revealed substantially higher FW-WM in the NLE group compared to the HC group (F = 4.666, p = 0.033). Additionally, FW-WM was negatively correlated with age of onset (r = −0.463, p < 0.001) and positively associated with seizure control in children with NLE (r = 0.306, p = 0.012). Conclusion: Children with NLE have reduced glymphatic system function, and the underlying pathophysiologic mechanisms may be due to impaired interstitial fluid clearance and retention in the brain. DTI-ALPS and free-water mapping are useful noninvasive approaches for examining glymphatic function in children with NLE, with the FW-WM potentially serving as an imaging marker for disease progression and predicting clinical prognosis in children with NLE.